2006
DOI: 10.1097/01.ana.0000210999.18033.f6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Ischemic Events After Severe Traumatic Brain Injury in Humans: A Simple Scoring System

Abstract: The ischemic score proposed here, may be determined during the acute intensive care unit period, and correlates closely with outcome, which can only be determined 3 to 6 months, after injury. It also shows a correlation with neurochemical analytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Thirteen studies documented an association between CMD measured glucose and mortality/Glasgow Outcome Scale (GOS) at 3–6 months [ 6 , 9 , 29 , 38 , 48 , 54 , 64 , 66 , 73 , 80 , 105 , 107 , 108 ]. The documented association was that low CMD glucose was associated with patient functional outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies documented an association between CMD measured glucose and mortality/Glasgow Outcome Scale (GOS) at 3–6 months [ 6 , 9 , 29 , 38 , 48 , 54 , 64 , 66 , 73 , 80 , 105 , 107 , 108 ]. The documented association was that low CMD glucose was associated with patient functional outcome.…”
Section: Resultsmentioning
confidence: 99%
“…This secondary damage is the result of a sequence of events that can include: disruption of the normal regulation of cerebral inflow and outflow, often resulting in cerebral hyperaemia; increased transmural pressure in capillary beds causing tissue hypoxia, elevated levels of CO 2 and a reduction in extravascular fluid resorption; tissue acidosis; metabolic dysfunction; microthrombus formation; secondary inflammation, and damage to the blood-brain barrier, all of which increase cerebral oedema and cause further increases in ICP [32,33,34,35,36,37,38,39,40,41,42,43]. The brain of a child, and particularly of a young child, may be particularly susceptible to these pathophysiological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a large population of TBI patients, Bullock and coworkers demonstrated that the results of microdialysisbased neurochemical monitoring correlate with quantitation of ischemic events, as measured by a simple five-item scoring system, taking into account the occurrence of specific potentially brain-damaging events (hypoxemia, hypotension, low cerebral blood flow, herniation, and low CPP). 14 Recently, in a population of TBI patients undergoing spreading depolarization (SD) monitoring, with electrocorticography, the association of SD and neurochemical markers as measured by microdialysis were studied. 15 The authors showed that extracellular glutamate (50 µmol/L) and lactate (3.7 mmol/L) were significantly elevated on day 0 in patients with SD.…”
Section: Microdialysis As a Measure Of Brain Energy Metabolism Alteramentioning
confidence: 99%